Numerical Approximation of Transcritical Simple Bifurcation Point of the Navier-Stokes Equations (Journal of Computational Mathematics, 2004)
The extended system of nondegenerate simple bifurcation point of the Navier-Stokes equations is constructed in this paper. Due to its derivative has a block lower triangular form, we design a Newton-like method. Using the extended system and splitting iterative technique to compute transcritical nondegenerate simple bifurcation point, we not only reduce computational complexity, but also obtain quadratic convergence of algorithm.
Keywords: Nondegenerate simple bifurcation point; Splitting iterative method; The extended system.